EphrinB2 regulates the emergence of a hemogenic endothelium from the aorta - Chen, Inn-Inn (Sci Rep, 2016)
Adult-type intraembryonic hematopoiesis arises from specialized endothelial cells of the dorsal aorta (DA). Despite the critical importance of this specialized endothelium for establishment of hematopoietic stem cells and adult hematopoietic lineages, the mechanisms regulating its emergence are incompletely understood. We show that EphrinB2, a principal regulator of endothelial cell function, controls the development of endothelium producing adult-type hematopoiesis. The absence of EphrinB2 impairs DA-derived hematopoiesis. Transmembrane EphrinB2 and its EphB4 receptor interact in the emerging DA, which transiently harbors EphrinB2(+) and EphB4(+) endothelial cells, thereby providing an opportunity for bi-directional cell-to-cell signaling to control the emergence of the hemogenic endothelium. Embryonic Stem (ES) cell-derived EphrinB2(+) cells are enriched with hemogenic endothelial precursors. EphrinB2 silencing impairs ES generation of hematopoietic cells but not generation of endothelial cells. The identification of EphrinB2 as an essential regulator of adult hematopoiesis provides important insight in the regulation of early hematopoietic commitment.